The Role of Public Infrastructure for Firm Location and International Outsourcing - Hartmut Egger; Josef Falkinger (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper presents a model in which final goods producers outsource intermediate input production. Intermediate inputs are differentiated and their production can be located at home or abroad. The model is used to examine competitive location policy in a (two-country) free trade agreement (FTA). It is shown that national public infrastructure investment has a positive effect on both the number of intermediate input producers and the return to the immobile factor in the home country. International outsourcing from home declines. Opposite effects are triggered in the partner country. In a welfare analysis we characterize national infrastructure policies that aim to maximize national income (net of tax costs) and compare the non-cooperative FTA-equilibrium with optimal policies from an integrated point of view. It is shown when coordination of competitive location policies is useful and when it is not.
Keywords: 330; international outsourcing; firm location; public infrastructure; welfare effects